Analysis of hotspots in the state of Pará from 2016 to 2019 (Research, Society and Development, 2022)
This work aimed to analyze the incidence of hotspots located in the state of Pará, from 2016 to 2019. For analysis, the hotspots that occurred in the state of Pará were mapped, highlighting the mesoregions with the highest occurrence. Statistical variables of measures of central trends were used, as well as maps were generated through the Kernel density estimator. For data manipulation, GIS system software was used. Maps were generated with five kernel density levels represented by colors, which are dark green (very low), light green (low), yellow (medium), orange (high) and red (very high), which is applied to the three municipalities with the highest number of outbreaks. The results showed that in Pará the incidence of hotspots is concentrated, above all, along the access roads. The mesoregions that had the highest incidence of hotspots are Southeast Pará (38,989), followed by Southwest Pará (38,411), Baixo Amazonas (16,547) and Northeast Pará (16,294). The municipalities that had a high incidence of hotspots are located in the mesoregions with the highest concentration, namely São Félix do Xingu (13,077) and the municipalities of Altamira (11,710) and Novo Progresso (6,840). The hotspots tend to increase in the driest months of the year, this increase starts from the month of July, with the month of November being the most critical.